Le concept de « marchandise fictive », pierre angulaire de l'institutionnalisme de Karl Polanyi ? - Postel, Nicolas; Sobel, Richard (Revue de philosophie économique, 2011)
The notion of “fictitious commodities” is not simply a convenient heterodox slogan to criticize the radical limits of any trade system and the analytical limits of the dominant theory. It is rather the foundation of the institutional perspectives that underlie all Karl Polanyi’s sociohistoric analyses. This article explains and articulates both the theoretical level using the institutional approach to commodities and a philosophical level using a broad definition of the economy. There is, however, a limit to the notion of the institution, which connects both levels: it is not articulated practically such that the potential and critique of this construct may be weakened.
Sociology; Economics
Keywords: capitalisme; institution; marchandises fictives; raison pratique; économie substantive

Avez-vous lu Polanyi ? - Maucourant, Jérôme (HAL, 2011)
"Cette étude présente le parcours intellectuel de Karl Polanyi (1886-1964), à la croisée de l'économie, de l'histoire et de la sociologie, et propose une synthèse de l'ensemble de son oeuvre." Postface accessible en ligne : [ http://www.contretemps.eu/lectures/bonnes-feuilles-avez-vous-lu-polanyi-j%C3%A9r%C3%B4me-maucourant-postface ]
Economics; Sociology
Keywords: Great Transformation; The (Book); La Grande Transformation; critique and interpretation; critique et interprétation; libéralisme; économie politique

Polanyi contre Freeman. (Polanyi against Freeman. With English summary.) - Postel, Nicolas; Sobel, Richard (Revue de la Regulation, 2011)
The dominant approach of CSR is based on the concept of "stakeholders" (R. E. Freeman). More than a theory, it is a slogan which irrigates as much the scientific discourse as the manager and political discourses. We can make two readings of this slogan. The first one, which is very reducing for us, consists on the deconstruction of the firm as institution and its replacement by a market representation based on bilateral exchanges between rational individuals. The second one, more promising in order to identify the potentialities of CSR in terms of regulation, intends to found the notion of stakeholder on a theory of actor and institution. It is the position which we defend by mobilizing Karl Polanyi's institutionalism.
Sociology; Economics
Keywords: Marxian; Sraffian; business objectives of the firm; corporate culture; current heterodox approaches: institutional; current heterodox approaches: socialist; diversity; evolutionary; social responsibility